Botany, morphology, ecology, cultivation, traditional utilization and conservation of andaliman (Zanthoxylum acanthopodium) in North Sumatra, Indonesia - YATI NURLAENI; DECKY INDRAWAN JUNAEDI; JOHAN ISKANDAR (Nusantara Bioscience, 2024)
Abstract. Nurlaeni Y, Junaedi DI, Iskandar J. 2024. Botany, morphology, ecology, cultivation, traditional utilization and conservation of andaliman (Zanthoxylum acanthopodium) in North Sumatra, Indonesia. Nusantara Bioscience 16: 68-80. This study examines the botany, ecology, cultivation, utilization, and traditional conservation of andaliman (Zanthoxylum acanthopodium DC.) in North Sumatra, Indonesia. This information were collected through in-depth interviews. The collected data consisted of primary and secondary data. Primary data were obtained in the field through in-depth interviews, participatory observation, and documentation. Meanwhile, to strengthen the results of the interviews, a literature study was conducted, which was obtained from academic sources that can be scientifically accounted for it grows naturally in relatively cool forests, foothills, and cultivated areas. Z. acanthopodium is distributed around Lake Toba at 800-1,300 masl (meters above sea level), a temperature 17-22°C, and a 5-40% slope. In North Sumatra, there are nine varieties: Siholpu, Siganjangpat, Sihalus, Sihorbo, Simanuk, and Sirangkak, and three varieties that have not been named yet. Z. acanthopodium is planted by maintaining wild plants, burning the land to be planted, collecting dead or old parts of the plant then burned, and collecting mature seeds as material for seeding then burned. The plant does not require fertilization and pesticides. The preservation of Z. acanthopodium in North Sumatra is based on local communities' traditional agricultural and ecological management.